A cascaded converter using hybrid cells and H-bridge structure - Satya Subrahmanya Ajay Dangeti; Chaitanya Kishore Patnaik Sekharamantry; Venkata Kowshik Bayanti; B. A. Raju Ch; KVS Ramachandra Murthy; Abhilash Tirupathi (Bulletin of Electrical Engineering and Informatics, 2021)
This paper introduces a cascaded converter structure using hybrid two-level cells to form a single-phase seven-level inverter. Compared to various conventional and existing multilevel (MLI) topologies, this topology requires a lower number of devices. It uses several DC sources integrated in two-stage cells to provide the required voltage. In this topology, the DC-link condensers are not necessary. The modes of operation and modulation of the structure proposed are described in depth. Finally, in the MATLAB/Simulink platform the new topology is evaluated and the results reported.